The Effectiveness of Using Chronological Paragraph Strategy toward Students’ Writing Skills - Siti Wahyu Puji Anggraini; Lume Lume (Journal of Languages and Language Teaching, 2021)
This study aims to identify the effect of chronological order strategy on improving students' ability in writing paragraphs. The sample of this study was 40 students of SMPN 9 SATAP Pujut Central Lombok. This study employed a pre-experimental method by using intact-group comparison.  To gather the data, the pre-test and post-test were distributed to the groups to collect the writing score and the percentage of students’ writing classification. Analysis of Variance (ANOVA) was applied to testing the hypothesis. The finding data shows that there was enhancement of students’ classification in writing between pre-test and post-test. In pre-test the average of students’ classification between fair, poor and very poor. But in post-test the average of students’ classification improved into very good, good, fair and poor. The result of data analysis indicates a significant effect of using chronological order to improve students’ writing ability. It evidenced by the significant level was lower than 0.05 (0.00<0.05).